Analyzing patterns of economic growth: a production frontier approach - Monika Kerekes (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
The growth experience of virtually all but the very rich countries is best explained as a combination of high and low growth episodes. Therefore, there is a need to under- stand the sources of growth during high and low growth regimes and in particular the influences as growth regimes change. This paper approaches the issue by combining the derivation of structural breaks in economic growth with nonparametric growth accounting that enables the decomposition of productivity changes into technological and efficiency changes. The results show that even in the medium run growth rate changes are mainly the result of productivity changes whereas factor accumulation plays only a minor role. Except for high income countries productivity changes usually represent e±ciency changes. A comparison of growth take-offs and growth collapses reveals that factor accumulation is even less important in periods of accelerating growth.
Keywords: O11; O47; 330; Growth; Structural Breaks; Data Envelopment Analysis; Wirtschaftswachstum; Technische Effizienz; Data-Envelopment-Analyse; Strukturbruch; Produktivität; Welt